Examining influencing factors and their hierarchical relationships in flight crew resilient behavior through a hybrid ISM-DEMATEL approach - Peng He; Fei Lu; Ruishan Sun; Zhaoning Zhang (Scientific Reports)
Abstract The increasing complexity of aviation systems and the rise of unpredictable “Black Swan” events necessitate resilience-based safety management strategies. Flight Crew Resilient Behavior (FCRB), defined as the ability of flight crews to adapt effectively beyond standard operating procedures, is critical for ensuring operational safety. Despite its significance, systematic approaches to understanding and managing FCRB remain underdeveloped. This study builds on American Airlines’ pioneering work by extending the FCRB scope to the Chinese aviation sector, and identifies 22 key factors influencing FCRB across individual, cockpit, organizational, and social dimensions through a comprehensive literature review and expert interviews. A hierarchical model was developed using Interpretive Structural Modeling (ISM) to uncover the relationships and layered dependencies among these factors. Subsequently, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was applied to analyze causal relationships and interaction strengths, pinpointing critical driving and dependent factors within the system. The integrated ISM-DEMATEL analysis revealed seven management pathways, offering actionable strategies to enhance FCRB through targeted interventions in knowledge development, safety culture, and responsibility. These findings provide a robust framework for airlines, aviation authorities, and manufacturers to manage FCRB proactively, address both anticipated and unforeseen challenges, and advance aviation safety.